Cerebral cortex assembly: generating and reprogramming projection neuron diversity - Lodato, Simona (Trends Neurosci, 2014)
The mammalian cerebral cortex is responsible for the highest-levels of associative, cognitive and motor functions. In the CNS, the cortex stands as a prime example of extreme neuronal diversity, broadly classified into excitatory projection neurons and inhibitory interneurons. Here, we review recent progress made in understanding the strategies and mechanisms that shape projection neuron diversity during embryogenesis and discuss how projection neuron classes may be maintained, postnatally, for the life of the organism. In addition, we consider the intriguing possibility that projection neurons may be amenable to directed reprogramming of their class specific features to allow enhanced cortical plasticity in the adult.